2002
DOI: 10.1103/physrevb.65.155303
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Rashba spin splitting in two-dimensional hole systems

Abstract: It has long been assumed that the inversion asymmetry-induced Rashba spin splitting in two-dimensional (2D) systems at zero magnetic field is proportional to the electric field that characterizes the inversion asymmetry of the confining potential. Here we demonstrate, both theoretically and experimentally, that 2D heavy hole systems in accumulation layer-like single heterostructures show the opposite behavior, i.e., a decreasing, but nonzero electric field results in an increasing Rashba coefficient.Comment: 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
163
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(171 citation statements)
references
References 17 publications
8
163
0
Order By: Relevance
“…Recently, it has also been proposed 7 that hole-doped nanowires, because of the possibly stronger spin-orbit coupling 22,23 and larger effective mass of holes, might be a better candidate for creating topological superconductors and Majorana fermions. The hole-bands of a group III-V semiconductor such as InAs or GaAs are composed of p-orbitals, which have orbital angular momentum L = 1.…”
Section: B Hole-doped Semiconductorsmentioning
confidence: 99%
“…Recently, it has also been proposed 7 that hole-doped nanowires, because of the possibly stronger spin-orbit coupling 22,23 and larger effective mass of holes, might be a better candidate for creating topological superconductors and Majorana fermions. The hole-bands of a group III-V semiconductor such as InAs or GaAs are composed of p-orbitals, which have orbital angular momentum L = 1.…”
Section: B Hole-doped Semiconductorsmentioning
confidence: 99%
“…We obtained α 3 ¼ 2.26 × 10 5 e Å 4 . The coefficient α 3 is about 1 order smaller than for the 2DHG in the GaAs/AlGaAs single heterostructure [21], which is a nearly lattice matched system. The smaller α 3 value is due to the large HH-LH separation in Ge=Si 0.5 Ge 0.5 compared to that of the GaAs/AlGaAs structure; the large HH-LH separation decreases the coefficient α 3 .…”
mentioning
confidence: 99%
“…For example, in case of the spin Hall effect, the k-cubic Rashba term is predicted to give rise to a larger spin Hall conductivity [17][18][19]. Recently, the cubic-Rashba SOI has been reported in a two-dimensional hole gas (2DHG) in inversion asymmetric semiconductors InGaAs and GaAs [20,21], and a twodimensional electron gas formed at a surface of the inversion symmetric oxide SrTiO 3 [15]. However in the former case, the InGaAs and GaAs possess both BIA and SIA; thus, they are always influenced by both Dresselhaus and Rashba SOI contributions [22].…”
mentioning
confidence: 99%
“…In a previous study [20] this surprising behavior of β h 1 E ⊥ was shown as a function of density. By lowering the density, spin splitting and E ⊥ both decrease but the term β h 1 E ⊥ increases.…”
mentioning
confidence: 99%